Telenursing With Wa-Reminder for Edu-Anemia and Fe Medication Adherence - Marliany, Heni; Rahman, Irpan Ali; Nurfaujiah, Diny; Masru’ah, Iim Imas; Salam, Wulan Anugrah Fauzi (GLOBAL HEALTH SCIENCE GROUP, 2024)
The development of modern technology in the form of increasingly sophisticated use of smartphones is making it important for various activities, especially in the health sector, often referred to as telenursing. Telenursing, through the use of the WA-Reminder application with messaging for adolescents suffering from anemia, is a solution that can be used by health workers to increase education related to anemia and monitoring of FE medication use in an effort to maintain HB levels within normal limits.. Aims: the purpose of this study is to determine the effectiveness of Telenursing With Wa-Reminder For Edu-Anemia and Fe Medication Adherence in SMA Negeri 2 Ciamis 2023. Method: the research method used was a quasi-experimental one group pretest-posttest design. The study population included all adolescent girls with anemia at SMA Negeri 2 Ciamis using a non-probability sampling technique. The instruments used were a mobile phone as a container for the Whatssap application, a questionnaire that had been tested for validated and reliable with Cronbach's alpha values 0.769 to measure adolescents' knowledge about anemia, and an observation sheet to measure compliance with FE medication. Data were analysed using univariate and bivariate techniques. Results: The results of the paired t-test showed that students' knowledge of anemia and compliance in taking FE medication were 0.039 and 0.000, respectively (p < 0.05). Conclusions: Telenursing with WA-Reminder is effective in improving knowledge and compliance with FE medication among adolescents with anemia.